Improving Students' Speaking Skill through Snowball Throwing Technique (STT) at Indonesian Junior High School - Delmus Puneri Salim; Fadhlan Saini; Farmi Paputungan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This research is a Classroom Action Research (CAR).  It aimed at improving students’ speaking skill of the 7th grade at SMP N 1 Kotabunan East Bolaang Mongondow through the snowball throwing technique. The subjects of this research were 31 students consisted of 21 girls and 10 boys. But, only 25 students who attended the classroom. In this research, the researchers used mixed method (quantitative and qualitative design). To collect the data, the researchers utilized by using tests and observation. The researchers conducted the tests by asking the questions that related to the lessons that students had previously learnt.  Meanwhile, observation was accomplished in order to observe qualitatively about the students’ learning process by the technique. The results showed that, in the first cycle, the mean score was 39.84 with percentage of students who passed the test was 52%. While in the second cycle, the mean score of post-test was 72.16 with the percentage of students who passed the test was 100%. According to the observation in the first cycle, it revealed that students could not carry out the technique properly and some students were not good in speaking such as having bad grammar and pronunciation. Furthermore, the researchers used the papers to construct as a ball in conducting the snowball throwing technique. In the second cycle, it indicated that the students were going better by carrying out the following technique. Based on the indication of the result, it can be said that there was an improvement of students’ speaking skill through snowball throwing technique of the 7th grade at SMP N 1 Kotabunan East Bolang Mongondow.